Leadership for Change in Teacher Education: Voices of Canadian Deans of Education - Elliott-Johns, Susan E (Springer, 2016)
Leadership for Change in Teacher Education: Voices of Canadian Deans of Education presents a rich sampling of diverse perspectives on the topic in a unique collection of reflections contributed by Canadian deans of education. The focus of the inquiry, “What would we hear from deans of education invited to share their perspectives on leadership for change in contemporary teacher education?” invited deans of education to reflect on the research, policies and practices currently informing their leadership. The results, fourteen engaging and provocative essays, offer important insights and increased understandings of the complex nature of their work and explore concerns raised in relation to lived experience and the multi-faceted processes of leading change for teacher education in contemporary contexts. Reflections in these short essays underscore the critical role of deans in provoking, supporting and championing new ideas and approaches to pedagogy for teacher education, and make clear the complexities inherent in leading the change. The Coda highlights the limited scope of related research available in the current literature and recommends urgent attention, in both research and practice, to the preparation of deans and support for their ongoing professional learning and sustainable leadership.